The Incremental Information Content of Capital Expenditures. - Kerstein, Joseph; Kim, Sungsoo (The Accounting Review, 1995)
Studies whether capital expenditures provide value relevant information which is incremental to that of current earnings. Value relevance of individual firm factors; Development of factors for risk and growth; Sensitivity of predisclosure information on capital expenditures to the firm's size.